The Effects of the Hybrid Telerehabilitation Exercise Program in Inactive University Students during COVID-19 Pandemic – A Randomized Controlled Study - Özer, Aysel Yildiz; Şenocak, Emre; Aybey, Buse Nur; Tolmaci, Leonid; Sürmeli, Şahzenan; Özmen, İpek; Polat, Mine Gülden (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Background/Aim The need for alternative methods to prevent physical inactivity and related problems is increasing day by day due to the prevalence of physical inactivity among university students, especially in the pandemic. This study aimed to investigate the effects of a hybrid telerehabilitation exercise program on the physical inactivity, poor sleep quality and physio-mental negativities caused by the pandemic in university students.Materials and Methods The study was completed with sixty-three physically inactive students with poor sleep quality, divided into two groups. The physiotherapist made all assessments at baseline and after the 6-week for both groups. Assessments consisted of Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI), Short Form-12 (SF-12), and International Physical Activity Questionnaire-Short Form (IPAQ-SF). While no exercise program was applied to the control group, one session synchronous exercise training and one session control education were given to the exercise group. After two synchronous training sessions, the exercise group asynchronously continued the exercise program including indoor walking, flexibility and strengthening exercises for 6 weeks.Results According to inter-groups analysis, PSQI (p=0.026), BDI (p=0.037), SF-12 Mental (p=0.007), and IPAQ-sitting (p=0.003) of the exercise group had significant differences compared to the control. Also, the exercise group's PSQI, BDI, SF-12, and IPAQ-sitting time were p<0.001, while no change was observed in the control group in the within-group analysis (p>0.05).Conclusion Hybrid telerehabilitation exercise programs are a valuable, simple, and practical tool to improve sleep quality, prevent inactivity, develop and protect mental health among university students. Encouraging physically inactive people to engage in such methods may be one of the primary preventive approach to prevent the future negative consequences.
Keywords: Hybrid Telerehabilitation; sleep quality; depression; physical inactivity; exercise